2019
DOI: 10.3389/fenvs.2019.00107
|View full text |Cite
|
Sign up to set email alerts
|

Fire-Regulating Services and Disservices With an Application to the Haifa-Carmel Region in Israel

Abstract: In the Mediterranean region, and in other fire-prone areas of the globe, the risk of human and economic losses due to forest fires has increased in the past decades, particularly at the urban-wildland interface. To counter this trend, economic and human resources are generally invested to combat and suppress wildfires, with much less invested to adapt through ecosystem-based management. Ecosystem services for fire regulation are rarely accounted for in the literature and are generally excluded from ecosystem s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 105 publications
(132 reference statements)
1
12
0
Order By: Relevance
“…Donovan et al (2017) reported increased frequency and size of large grassland wildfires in the US Great Plains in the early 21st century compared to late 20th century. Prescribed fire is a common management tool within extensive grasslands and therefore regulates intensity, severity, and fire return intervals in the landscape, helping to reduce largescale, high-intensity fires and associated damage to humans and the environment (Depietri and Orenstein 2019) while enhancing or maintaining v www.esajournals.org several ecosystem services. In contrast, fire may be less critical in cultivated grasslands when biomass removal associated with intensive grazing reduces fuel loads (Ellis et al 2005, McGranahan et al 2012.…”
Section: Fire Regulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Donovan et al (2017) reported increased frequency and size of large grassland wildfires in the US Great Plains in the early 21st century compared to late 20th century. Prescribed fire is a common management tool within extensive grasslands and therefore regulates intensity, severity, and fire return intervals in the landscape, helping to reduce largescale, high-intensity fires and associated damage to humans and the environment (Depietri and Orenstein 2019) while enhancing or maintaining v www.esajournals.org several ecosystem services. In contrast, fire may be less critical in cultivated grasslands when biomass removal associated with intensive grazing reduces fuel loads (Ellis et al 2005, McGranahan et al 2012.…”
Section: Fire Regulationmentioning
confidence: 99%
“…Long-term data from native perennial grasslands across the Great Plains, USA, suggest a fire return interval of ~2.59 yr (Allen and Palmer 2011), and these frequent fires are important in reducing litter and debris, invasive species, and woody encroachment (Depietri and Orenstein 2019). Noss (2012Noss ( , 2018 reports even more frequent fire return intervals of 1-2 yr for southeastern US grasslands in regions of intense lightning activity.…”
Section: Fire Regulationmentioning
confidence: 99%
See 3 more Smart Citations